Ischemia–Reperfusion Injury at Time-Zero Biopsy as a Prognostic Factor in Predicting Liver Graft Outcome in Egyptian Living Donor Liver Transplanted Patients - Aliaa Sabry; Hazem Zakaria; Doha Maher; Randa Mohamed Seddik; Ali Nada (International Journal of Hepatology)
Conclusion: Time-zero biopsies with moderate to severe IRI upon biopsy can predict adverse clinical outcomes following LT.